Effect of hempseed products on growth performance, carcass yield, omega-3, and omega-6 fatty acids in broiler: A meta-analysis - Y Sopian; Panneepa Sivapirunthep; Chanporn Chaosap (IOP Conference Series Earth and Environmental Science, 2024)
Abstract Hempseed is the edible fruit of the Cannabis sativa L. plant, potentially serving as feed ingredients in broiler production due to its high nutritional value. Therefore, this meta-analysis aimed to determine the effect of hempseed products (seeds, cakes, or oils) on body weight (BW), feed intake (FI), feed conversion ratio (FCR), carcass yield (CY), and fatty acid (FA) composition (ω-3 and ω-6) in broiler chicken. Ten eligible publications were retrieved from Google Scholar and Scopus databases for the meta-analysis. The random-effects model was used for data analysis in OpenMEE software. Results were expressed as standardized mean differences (SMD) at 95% confidence intervals (CI). Results show that dietary hempseed products increased ω-3 FA (SMD = 1.107; P<0.05) and ω-6 FA (SMD = 0.987; P<0.01) but reduced BW (SMD = -0.403; P<0.05) and FI (SMD = -0.470; P<0.05) compared to the controls. On the other hand, CY (SMD = 0.053; P>0.05) and FCR (SMD = 0.046; P>0.05) were not significantly influenced by hempseed product supplementation. Subgroup analysis revealed that hempseed oil reduced BW (SMD = -1.041; P<0.05) and FCR (SMD = -0.797; P<0.05) but enhanced both ω-3 FA (SMD = 2.372; P<0.01) and ω-6 FA composition (SMD = 1.630; P<0.01). There were no adverse effects of hempseed and hempseed cake on BW (P>0.05), but a higher FCR (SMD = 0.658; P<0.05) was obtained on broilers fed with hempseed. Moreover, dietary hempseed and hempseed cake also increased ω-3 FA (SMD = 0.952; P<0.05) and ω-6 FA composition (SMD = 1.107; P<0.01), respectively. This study concluded that dietary hempseed products had beneficial effects on the fatty acid composition of meat. However, its effect on growth performance should be considered.
Keywords: Animal Nutrition and Physiology; Cassava research and cyanide; GABA and Rice Research